How does Learning Drama Help Students to Build Seven Survival Skills? - Een Nurhasanah (Budapest International Research and Critics University, 2022)
This study aims to answer the question how does drama learning help students develop the Seven Survival Skills? The method used in the research is the qualitative approach used in this study to describe in detail. The researcher uses the theory